Classifying Far-Right Groups as Gangs. (November 2021) - Valasik, Matthew; Reid, Shannon E.
The uneven response by law enforcement has resulted in the overall under-policing of far-right groups. Policy makers and the broader criminal justice system need consider proactive approaches if the goal is to prevent violence from far-right groups. A straightforward and appropriate approach is to treat far-right groups as street gangs. Existing gang statutes are a proven tool is aggressively used on BIPOC gangs and should be equally applied to far-right groups. Law enforcement's continued dismissiveness of far-right groups only increases them as being the most "persistent and lethal threat" in the United States for the foreseeable future.